HUBUNGAN HARGA DENGAN KEPUASAN PASIEN DI RUMAH SAKIT BHAKTI MEDICARE, CICURUG, KABUPATEN SUKABUMI - Hasrul Hasrul (Universitas Pakuan, 2019)
The purpose of this study is to determine the presence or absence of price relationships with patient satisfaction in Bhakti Medicare, Cicurug, Sukabumi. The population of this research is 130 Bhakti Medicare’s patients, Cicurug, Sukabumi consisting of patients in Jasmine Room, Rose Room, Dahlia Room and Orchid Room. This amount fulfills the minimum sample for Slovin formula. The collected data is then processed using simple correlation and multiple correlation techniques using SPSS software. The results show that there is positive relation between price and satisfaction with correlation coefficient value equal to (ry.1) = 0,679, while price contribution to patient satisfaction equal to r2 = (ry.1)2 = 46,2%. In addition, price contribution is considered strong against patient satisfaction which means increased price will ensure patient satisfaction in Bhakti Medicare hospital, Cicurug, Sukabumi regency. In the most important dimension of price variable, the relationship is the dimension of